Cellular mechanisms of fibrin (ogen): insight from neurodegenerative diseases - Wen, Tingting; Zhang, Zhaohui (Frontiers in Neuroscience, 2023)
Neurodegenerative diseases are prevalent and currently incurable conditions that progressively impair cognitive, behavioral, and psychiatric functions of the central or peripheral nervous system. Fibrinogen, a macromolecular glycoprotein, plays a crucial role in the inflammatory response and tissue repair in the human body and interacts with various nervous system cells due to its unique molecular structure. Accumulating evidence suggests that fibrinogen deposits in the brains of patients with neurodegenerative diseases. By regulating pathophysiological mechanisms and signaling pathways, fibrinogen can exacerbate the neuro-pathological features of neurodegenerative diseases, while depletion of fibrinogen contributes to the amelioration of cognitive function impairment in patients. This review comprehensively summarizes the molecular mechanisms and biological functions of fibrinogen in central nervous system cells and neurodegenerative diseases, including Alzheimer’s disease, Multiple Sclerosis, Parkinson’s disease, Vascular dementia, Huntington’s disease, and Amyotrophic Lateral Sclerosis. Additionally, we discuss the potential of fibrinogen-related treatments in the management of neurodegenerative disorders.